Analysis of Aluminium Alloy 6061 Material Coating with the Addition of Malonic Acid Additive in the Plasma Electrolytic Oxidation Method to Improve Corrosion Resistance Properties - Lubis, Muhammad Ihsan; Mutmainnah; Kamil, Muhammad Prisla; Suwondo, Kusuma Putri; Asriyani, Nur; Lantang, Jessica Valenthine (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Aluminum alloy 6061 is extensively used in structural and engineering applications due to its favorable strength-to-weight ratio, good mechanical properties, and inherent corrosion resistance. However, it remains vulnerable to localized corrosion, especially in chloride-rich environments. This study investigates the effect of malonic acid (MA) as an organic additive in the Plasma Electrolytic Oxidation (PEO) process to enhance the corrosion resistance of aluminum alloy 6061. The experimental results indicate that the presence of MA reduces plasma initiation time, stabilizes discharge behavior, and facilitates the formation of a denser and more uniform oxide layer. Surface morphology analysis reveals that PEO coatings with MA exhibit finer porosity and a thicker structure, contributing to improved barrier properties. XRD characterization confirms the presence of stable crystalline phases such as mullite and andalusite in the MA-enhanced coatings. Electrochemical testing via Tafel polarization shows a significant reduction in corrosion current density (3.899 x 10-7 A/cm2) and corrosion rate (0.642 mm/year), alongside a more positive corrosion potential (-2.616 V) in the MA-treated samples. When compared to traditional corrosion inhibitors, both organic (for example, imidazole-based compounds) and inorganic (for example, CaCO3 and SiO2), the PEO plus MA method demonstrates superior long-term corrosion resistance and structural stability. These findings highlight the potential of malonic acid as an effective additive for optimizing the PEO process in demanding environmental conditions.